The Phase‐Locking of Tropical North Atlantic and the Contribution of ENSO. Issue 23 (30th November 2021) - Chen, Han‐Ching; Jin, Fei‐Fei; Jiang, Leishan
Abstract: The Tropical North Atlantic (TNA) is characterized by significant interannual variability in sea surface temperature (SST), which is phase‐locked to the boreal spring. In this study, the phase‐locking of TNA is investigated by adopting a linear stochastic‐dynamical model (SDM) using seasonally modulated TNA feedbacks together with the seasonal modulation of ENSO forcing. In the observations, the role of local TNA feedbacks and ENSO forcing in TNA phase‐locking are equivalently important with both preferring the peak of TNA variability to appear in the boreal spring. Besides, the seasonal modulation of TNA feedbacks and ENSO forcing strength are both mainly controlled by thermodynamic processes. In most climate models, the contribution of ENSO on TNA phase‐locking is weaker than that in observations. The strength of ENSO‐related TNA phase‐locking is highly correlated with the relationship between ENSO and TNA, which is mainly determined by the amplitude of ENSO and its teleconnection patterns. Plain Language Summary: The interannual variability of sea surface temperature (SST) in the Tropical North Atlantic (TNA) is a prominent climate mode occurring in the Atlantic. TNA SST anomalies usually grow during boreal winter, reach their maximum amplitude in boreal spring and then decay in the summer and fall, called TNA phase‐locking phenomenon. Although understanding the phase‐locking of TNA is important for predicting the TNA and determining the global TNA teleconnection, there is very little discussion of the mechanisms of TNA phase‐locking in the literature. In this study, we develop a conceptual stochastic‐dynamical model (SDM) using seasonally modulated TNA feedbacks with seasonal modulation of ENSO forcing to investigate the features and mechanisms of TNA phase‐locking. The SDM simulations can well reproduce the TNA phase‐locking for observations and CMIP models. The mechanisms of TNA phase‐locking and the contribution of ENSO on TNA phase‐locking are discussed. Key Points: By considering the seasonal modulation of local feedbacks and remote ENSO forcing, the SDM model can well reproduce the TNA phase‐locking In observations, the role of local TNA feedbacks and ENSO forcing are equivalently important in TNA phase‐locking The TNA phase‐locking strength associated with ENSO is highly correlated with the relationship between ENSO and TNA